Influence of medium ph on surfactant synthesis by Acinetobacter calcoaceticus IMV B-7241 on hydrophilic substrate ethanol - Antoniuk, Svitlana; Konon, Anastasia; Chebotaryova, Ksenia (My University, 2012)
The synthesis of exocellular metabolites with surface-active and emulsifying properties was investigated at the maintaining pH at 5.0-8.0 rate during the cultivation of Acinetobacter calcoaceticus IMV B-7241 on the medium with ethanol (2% by volume). It was stated that the maintaining pH at 7.0 by the KOH solution was accompanied by the increase of surfactant synthesis in 1.8 times comparing with the process without pH regulation. The replacement of KOH on NaOH for the maintaining pH at an optimal level led to the decrease of surfactant concentration in 1.2-1.5 times that was caused by the inhibitory effect of sodium cations on the activity of enzymes of surface-active amino- and glycolipids biosynthesis.
Keywords: кафедра біотехнології і мікробіології; Acinetobacter calcoaceticus ІМВ В-7241; pH regulation; регулирование рН; регулювання рН